Craving for Ketamine and Its Relationship With Clinical Outcome Indicators in Males With Ketamine Use Disorder - Wang, Peng-Wei; Lin, Huang-Chi; Liu, Tai-Ling; Hsu, Chih-Yao; Yang, Yu-Yi; Wu, Hung-Chi; Yen, Cheng-Fang (Frontiers in Psychiatry, 2021)
Background Craving is considered a hallmark of substance use disorder and is one of the criteria of substance use disorder. The Desires for Drug Questionnaire (DDQ) is a widely-used questionnaire to assess craving for heroin. This study aimed to examine the psychometric properties of the ketamine version of the DDQ (DDQ-K) and the associations between craving for ketamine as measured using the DDQ-K and clinical outcome indicators in individuals with ketamine use disorder. Methods In total, 651 individuals with ketamine use disorder completed the DDQ-K and the Visual Analog Craving Scale (VACS). Demographic data, severity of ketamine use, money spent on ketamine, positive/negative aspects of ketamine use, and readiness to change ketamine use were also recorded. We examined the reliability (internal consistency), construct validity (factor structure), and concurrent validity of the DDQ-K. Multiple regression analysis was used to examine the relationships of craving measured using the DDQ-K with clinical outcome indicators, including money spent on ketamine, severity of ketamine use, positive/negative aspects of ketamine use, and readiness to change ketamine use. Results The original three-factor model of the DDQ-K was acceptable for use in individuals with ketamine use disorder according to confirmatory factor analysis. The subscales of Desire and Intention and Negative Reinforcement of the DDQ-K, but not the subscale of Control, were of acceptable concurrent validity. The score on the Desire and Intention subscale was positively associated with the level of ketamine dependence, money spent on ketamine use, and positive/negative aspects of ketamine use, and negatively associated with readiness to change ketamine use. Conclusion This study supported the use of the Desire and Intention and Negative Reinforcement subscales of the DDQ-K to assess craving in patients with ketamine use.